RATIONALITY: NORMAL MENTAL FUNCTIONING OR PSYCHOLOGICAL COHERENCE? - Vasilionytė, Ieva (Problems / Problemos, 2012)
A version of the rationalist internalist argument, employing a pro tanto reading of the term "normative reason", is often criticized due to its conception of rationality. It is said that the condition of rationality is insufficient to secure the necessary relation between the moral judgement and the respective motivation to act. I claim that such a criticism is based on the false supposition that rationality is to be identified with normal mental functioning. It is shown that for the rationalist internalists rationality does and should rather amount to inner psychological coherence, and that the respective conception of irrationality can account for all the purported counterexamples to the motivational internalism. In addition, I pinpoint that "full rationality" is neither an intuitive notion nor a necessary condition for the rationalist internalism to hold, therefore, a line of criticism employing the notion misses the target.